2014
DOI: 10.1371/journal.pone.0085719
|View full text |Cite
|
Sign up to set email alerts
|

The GG Genotype of Telomerase Reverse Transcriptase at Genetic Locus rs2736100 Is Associated with Human Atherosclerosis Risk in the Han Chinese Population

Abstract: A single nucleotide polymorphism (SNP) in the second intron of human TERT (hTERT), rs2736100, acts as a critical factor in hTERT synthesis and activation. The rs2736100 SNP was found to be associated with susceptibility to many cancers. Recently, inhibition of telomerase and marked telomere shortening were determined to be closely associated with the increasing severity of atherosclerosis. The association between the SNP of rs2736100 and the presence of atherosclerosis was evaluated in 84 atherosclerosis patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…However, the present finding showed lack of association between the rs2736100 variants and PTB susceptibility, despite several studies revealing significant effects of this genetic variant on susceptibility to cancer, atherosclerosis, idiopathic pulmonary fibrosis, depression, etc. (Shete et al, 2009;Turnbull et al, 2010;Chen et al, 2012;Mocellin et al, 2012;Feng et al, 2014;Wei et al, 2015;Yuan et al, 2016). In summary, this study showed that PTB susceptibility is associated with the MCP-1 rs1024611 variant, but not with TERT rs2736100 SNPs.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…However, the present finding showed lack of association between the rs2736100 variants and PTB susceptibility, despite several studies revealing significant effects of this genetic variant on susceptibility to cancer, atherosclerosis, idiopathic pulmonary fibrosis, depression, etc. (Shete et al, 2009;Turnbull et al, 2010;Chen et al, 2012;Mocellin et al, 2012;Feng et al, 2014;Wei et al, 2015;Yuan et al, 2016). In summary, this study showed that PTB susceptibility is associated with the MCP-1 rs1024611 variant, but not with TERT rs2736100 SNPs.…”
Section: Discussionmentioning
confidence: 45%
“…Telomerase reverse transcriptase (TERT) is the rate-limiting catalytic component of telomerase, (Daniel et al, 2012;Kong et al, 2014) and there are multiple SNPs in the TERT locus, among which rs2736100 is the most studied (Mocellin et al, 2012;Yuan et al, 2016). The rs2736100 variant has been shown to be associated with several disorders (Shete et al, 2009;Turnbull et al, 2010;Chen et al, 2012;Mocellin et al, 2012;Feng et al, 2014;Wei et al, 2015Wei et al, , 2016Yuan et al, 2016). Biologically, rs2736100_CC stimulates TERT transcription, thereby enhancing telomerase activity (Wei et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Calpain is also involved in physiological and pathophysiological processes, including cytoskeletal reorganization, cell cycle regulation, signal transduction, and apoptosis pathway . rs2736100 of CAPN10 from GG genotype works as independent risk factor which is specially associated with the presence of arteriosclerosis . In addition, upregulation of CAPN10 exhibits its role in neurodegenerative diseases such as Alzheimer‐type disease, by enhancing the accumulation of β‐amyloid peptide, inducing the hyperphosphorylation in the central nervous system where it degenerates the neurologic functions .…”
Section: Introductionmentioning
confidence: 99%
“…10 rs2736100 of CAPN10 from GG genotype works as independent risk factor which is specially associated with the presence of arteriosclerosis. 14 In addition, upregulation of CAPN10 exhibits its role in neurodegenerative diseases such as Alzheimer-type disease, by enhancing the accumulation of β-amyloid peptide, inducing the hyperphosphorylation in the central nervous system where it degenerates the neurologic functions. 15 Moreover, it was proved that CAPN10 plays an important role in intellectual disability and cognitive impairment processes, from which we got inspired, although it is from a congenital disease perspective and the mechanism how CAPN10 works remains unclear.…”
mentioning
confidence: 99%
“…A variant in the second intron of TERT (hTERT) gene, rs2736100, play an important role in hTERT synthesis and activation. This variant was reported to be correlated with susceptibility to different types of cancer [13].There are studies reporting that variant rs2736100 T > G of the TERT gene was found to be correlated with shortened telomere length in several types of cancers, while in other studies no association between telomere length and rs2736100 was found [14,15].…”
mentioning
confidence: 99%